Penerapan Motivasi Kerja dalam Meningkatkan Kinerja Karayawan pada Kantor Notaris dan PPAT Karawang (International Forum of Researchers and Lecturers, 2025)
Human Resource Management is the development of human resource that carry out planning, implementation, recruitment, career development of employees, employees and carry out initiatives on organizational development in an organization, or company. This study aims to analyze the implementation of employee performance management in a notary office. Performance management is a systematic process of organizational goals. In the notarial work environment, performance management plays a crucial role in ensuring legal service are accurate, timely, and professional. This research uses a qualitative approach with data collection techniques including interviews, observations, and document analysis. The result indicate that performance management has been applied through the setting of work targets, monitoring of outcomes, and the provisions of evaluations and feedback. However some challenges remain, such as the absence of structured evaluation system and a lack of regular training. The conclusions of this study emphasizes the importance of developing a more formal and measurable work management system in order to increase employee motivation and overall performance. The implications of the research are expected to be a reference in human resource development in notary office and other legal service institutions.